Impact of inhalation vs. intravenous anaesthesia on autonomic nerves and internal anal sphincter tone. Issue 9 (21st April 2015) - Heid, F.; Kauff, D. W.; Lang, H.; Kneist, W.
<x xml:space="preserve">Abstract</x> Background Pelvic intraoperative neuromonitoring (pIONM) aims to identify and spare the autonomic nerves and maintain patients' quality of life. The effect of anaesthetic agents on the pIONM signal is unknown; therefore, the aim of the present study was to compare the influences of inhalation anaesthesia (IA) and total intravenous anaesthesia (TIVA). Methods Twenty rectal cancer patients undergoing open nerve‐sparing total mesorectal excision (TME) were assigned to pIONM under either IA or TIVA (n = 10 per group). IA was maintained with sevoflurane and TIVA with propofol. During surgery, pelvic autonomic nerves were electrically stimulated under electromyography (EMG) of the internal anal sphincter (IAS). These triggered EMG signals were analysed. Results The absolute EMG amplitude during pIONM increased to 1.20 μV (interquartile range (IQR): 0.94–1.6) for IA and 1.49 μV (IQR: 0.84–2.75) for TIVA (P = 0.002). The relative EMG amplitude increase also was significantly lower for IA (0.59; IQR: 0.30–0.81; TIVA: 0.99; IQR: 0.62–2.5), (P = 0.001). Conclusions This is the first study to compare the influences of IA and TIVA on the autonomic nervous system. While both anaesthetic regimens proved useful for pIONM, TIVA with propofol may provide better signal quality than IA with sevoflurane.